Academic library leaders’ conceptions of library leadership in Pakistan - Ashiq, Murtaza; Ur Rehman, Shafiq; Hina Batool, Syeda (Malaysian Journal of Library and Information Science, 2019)
The aim of the study is to investigate the conceptions of academic library leaders’ about library leadership, library management, the best attributes for academic library leaders and the ways to develop leadership skills. A qualitative approach was used and data were collected through in-depth interviews from 15 experienced academic library leaders in Pakistan. Phenomenology was used to explore the common conceptions of the participants about library leadership, library management, smart leaders’ attributes and significant ways to develop leadership. Academic library leaders perceived that a library leader is all about being visionary and innovative, being bold, and being a knowledge worker. Majority of the participants differentiated between library leader and library manager however, others had similar conceptions about both roles. The best attributes of academic library leaders conceived by professionals are having a humanistic and charismatic personality, being a team leader, and having building relationship skills or social outreach. Humanist aspect of a leader prevails among participants’ voices and this might be an addition to the existing literature. Continuous professional development, mentorship, and being in a competitive environment are the best ways for library leadership skills development. The study would be helpful for library leaders, university management, library associations and library schools in policy making and offering of professional training and education of library leaders.